ANALISIS KINERJA PETUGAS PPSU DALAM MENGOPTIMALKAN PELAYANAN KEPADA MASYARAKAT DI KELURAHAN BALEKAMBANG - Khairunnisa, Citra; Yasin, Yasnita; Irawaty, Irawaty (Universitas Djuanda, 2019)
This study aims to seek and analyze the performance of PPSU employees at kelurahan level in order to optimize public services, and the background of formation’s PPSU employees, particularly in Kelurahan Balekambang, Kramat Jati, East Jakarta. The research method which was applied in this research was descriptive with a qualitative approach. The data used were the results of observations, interviews, and documents studies carried to PPSU employees and Balekambang societies. The theory used in this research was performance theory from Kumorotomo. He argued that there are four indicators : Efficiency, Effectiveness, Justice, and responsiveness to scaling performances. Thus, this research found that the performance of the PPSU employees in Kelurahan Balekambang has been optimum since the first time the policy was implemented. It was based on the Governor’s Regulation of DKI Jakarta Number 7 of 2017 regards to Handling Public Infrastructure and Facilities in kelurahan level. However, the research also found that the society has not participated as stated in the Governor’s Regulation, as they have provided food from money which they collected. It can be concluded that the PPSU’s performances have been corresponded with the Governor’s Regulation, nevertheless what has not been fulfilled is the society’s participation. The participation which was stated in the regulation is actually in physical form, but the society agreed to participate in the other form. of money that is accommodated in the form of objects during community service.